Influenza vaccination in non-institutionalized elderly: a population-based study in a medium-sized city in Southern Brazil Vacinação contra a gripe em idosos não-institucionalizados: estudo de base populacional em município de médio porte do Sul do Brasil - Renata Maciulis Dip; Marcos A. S. Cabrera (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
Vaccination is the most effective measure to prevent the complications of influenza. This population-based study aimed to estimate influenza vaccine coverage in non-institutionalized elderly, analyze the factors involved in lack of influenza vaccine uptake, and identify post-vaccination adverse effects. The study population lived in an urban neighborhood in Southern Brazil, and the sample consisted of 425 elderly. A total of 396 elderly individuals (age 60-95 years) were interviewed. Although 100% of the sample reported knowing about the vaccine, only 5.3% referred to their personal doctor as the source of information. Among elders that had not received the vaccine, 83.2% were explicit about not wanting to take it. The main reasons were fear of adverse effects and disbelief in the vaccine's effectiveness. However, the actual prevalence of adverse effects was low. Age, smoking, and lack of a doctor's appointment in the previous year were independently associated with vaccine non-compliance. The results show that improvements are needed in the immunization campaign, especially targeting elders less than 70 years of age and smokers. A medida mais efetiva para evitar complicações da gripe é a vacinação. Os objetivos deste estudo de base populacional foram: estimar a cobertura vacinal contra a gripe em idosos não institucionalizados, analisar os fatores associados à não-adesão e identificar os eventos adversos pós-vacinais. A população de estudo foi constituída por idosos residentes em um município do Sul do Brasil. A amostra foi calculada em 425 idosos. Foram entrevistados 396 idosos, com idade entre 60 e 95 anos. Embora 100% dos idosos referissem conhecer a vacina, apenas 5,3% referiram o médico como fonte da informação. Dentre os que não se vacinaram 83,2% alegaram como motivo da não-adesão o desejo explícito de não ser vacinado. As principais justificativas para isso foram o medo de eventos adversos e a falta de credibilidade na eficácia da vacina. A prevalência de eventos adversos foi baixa. Idade, tabagismo e ter referido ausência de consulta médica no último ano associaram-se a menor adesão. Evidenciou-se a necessidade de melhorias nas campanhas vacinais para idosos abaixo de 70 anos e idosos tabagistas.